Impact of Social Media Marketing on Service Marketing in prospective of Pakistan’s Market - Haider, Zulqarnain; Khan, Khush Dil (iRASD Journal of Management, 2022)
In this study the impact of social media on service marketing for global service brands is check in Pakistan. The Social Media marketing has following important factors exposure, service quality, customer contact that has relationship with service marketing at two levels, effectiveness, and cost efficiency. A questionnaire is designed as per standard and data is collected from the population of Pakistan. The statistical analysis is done through the SPSS by applying ANOVA and other required tests. It is concluded from the quantitative study the social media marketing increases the outreach of the customer and result in improvement in service marketing of global service brands in Pakistan. The result of this study to be tested at big sample before generalizing the findings.